Chemoenzymatic Synthesis of Prenylated Indole Derivatives by Using a 4-Dimethylallyltryptophan Synthase from Aspergillus fumigatus - Steffan, Nicola; Unsöld, Inge A.; Li, Shu-Ming (Chembiochem : a European journal of chemical biology, 2007)
A 4‐dimethylallyltryptophan synthase, FgaPT2, has been identified in the genome of Aspergillus fumigatus. In a previous study, FgaPT2 was overexpressed in Saccharomyces cerevisiae and characterized biochemically. A higher protein yield (up to 100‐fold higher than that for S. cerevisiae) has now been achieved by overexpression in E. coli; this has permitted investigation into substrate specificity with alternative substances. FgaPT2 accepted 17 of 37 commercially available indole derivatives as substrates. Tryptophan derivatives that carry methyl groups at the indole ring showed a different acceptance from those with methyl groups on the side chain. 5‐Hydroxytryptophan was well accepted by FgaPT2, while the halogenated derivatives were not accepted. Decarboxylation, deamination, or oxidative deamination of tryptophan, as well as replacement of the NH2 group by OH, or of the COOH group by CH2COOH or CONHOH resulted in decreased but still significant enzymatic activity. None of the tested tryptophan‐containing dipeptides was accepted by FgaPT2. Structural elucidation of isolated enzymatic products by NMR and MS analyses proved unequivocally that the prenylation was regioselective at position C4 of the indole ring in the presence of dimethylallyl diphosphate. Determination of the kinetic parameters revealed that L‐tryptophan was accepted as the best substrate by the enzyme, followed by 5‐,6‐,7‐methyltryptophan and L‐abrine. The enzymatic rate constant (kcat Km−1) of nine selected substrates were found to be about 1.0 to 6.5 % of that for L‐tryptophan. Overnight incubation with eight substances showed that the conversion ratio to their prenylated derivatives was in the range 32.5 to 99.7 %. This provides evidence that 4‐dimethylallylated indole derivatives can be produced by chemoenzymatic synthesis with FgaPT2. High efficiency. FgaPT2, a 4‐dimethylallyltryptophan synthase from Aspergillus fumigatus, was used as a tool for chemoenzymatic synthesis. FgaPT2 accepted 17 of 37 indole derivatives as substrates, with conversion rates of up to 99.7 % being observed for eight selected indole derivatives. NMR and MS analyses proved that the prenylation was regiospecific at position 4 of the indole moiety. The kinetic parameters of nine indole derivatives were determined.